Implementation of the ASEAN Power Grid Interconnection West Kalimantan and Sarawak to Fulfill Electrical Energy Needs in Khatulistiwa - Savira Kamarani; Imam Supriyadi; Yanif Dwi Kuntjoro; Mochamad Fatchur Rozi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
West Kalimantan is a province in Indonesia that is directly adjacent to Sarawak, Malaysia. Electrical energy in West Kalimantan is not fulfilled because the source of electricity in West Kalimantan still relies on diesel which is expensive and cannot last all day, depending on the supply of fuel. Meanwhile, Sarawak has quite a large supply of energy coming from hydropower plants. To overcome the gap in those regions, ASEAN has made the West Kalimantan and Sarawak as one of the ASEAN Power Grid projects which connects certain areas in two different countries to share electricity supply. The purpose of this study is to determine the effectiveness of the cooperation between West Kalimantan and Sarawak electricity interconnection in meeting the electricity demand in the West Kalimantan region. In this research, the authors used qualitative methods by reviewing the literature. As the results of this study, the cross-border electricity interconnection cooperation between West Kalimantan and Sarawak is quite effective. By importing electricity from Sarawak the demand for electrical energy-especially in the main cities of West Kalimantan, can be fulfilled. So those two areas have the advantage where West Kalimantan is able to meet the electricity needs and Sarawak gets a profit margin by selling its electricity.